Fare casa in migrazione. Una chiave di lettura dei processi di integrazione e di riproduzione sociale quotidiana in contesti multietnici - Boccagni, Paolo (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2017)
Home as a place, and an assemblage of emotions and relationships associated with it, is central to everyday life. Its functions, meanings and accessibility are however far from obvious under the influence of major sources of social change such as international migration. The experience of home in circumstances of extended mobility and in multiethnic societies overall, opens up a promising space for empirical research. This article overviews it, building on a conceptualization of home as a way of feeling, understanding and “practicing” some places as distinct from all others. Importantly, though, individual and collective ways of “homing” evolve over time and space. The meanings, functions and transformations of home, whether among mobile or sedentary people, are affected by biographical, socio-cultural and structural factors, which call for an in-depth and comparative understanding.